Given the equation p = 2n – 3, what is p when=3
2 answers:
Plug in 3 for N
p= 2(3) - 3
p = 6 - 3
p = 3
Answer:
n = 3
Step-by-step explanation:
Hello!
p = 2n - 3
the question asks for when p is equal to 3 so we put 3 in for p
3 = 2n - 3
Now we can solve this
3 = 2n - 3
Add 3 to both sides
6 = 2n
Divide both sides by 2
3 = n
The answer is n = 3
Hope this Helps!
You might be interested in
Answer:25.1
Step-by-step explanation:
Answer:
the answer is c.
Step-by-step explanation:
4 x 5 + 7 x 7 = 69
4 x 3 + 7 x 9 = 75
Answer:
25%
Step-by-step explanation:
1/4×100
=25
.............
Simplify the expression and you get
~3x+6y
f(x) = x2 + 2x + 1, g(x) = 11x − 19 x<span>2 </span>+ 2x + 1 = 11x - 19 x2 - 9x + 20 = 0 (x-4)(x-5) = 0 x = 4, 5